Keberkesanan Kaedah “Mill and Pave” Asfalt dalam Penyelenggaraan Jalan di Johor - Khairul Arifin, Nurul Natasya; Omar, Roshartini (Research in Management of Technology and Business, 2025)
The “mill and pave” process involves the complete removal of the asphalt structure, milling to create a smooth surface, and the application of a fresh asphalt layer. However, poorly paved infrastructure and the use of low-quality tar often result in cracked or pothole-ridden roads, posing risks to road users. Therefore, this study aims to identify the challenges faced in using the “mill and pave” method, evaluate the effectiveness of the “mill and pave” method in road maintenance, and propose strategies to improve its application. Johor Bahru was chosen as the primary study location due to its high average daily traffic. A qualitative approach was employed in this study, involving interviews with the Public Works Department (JKR) and road maintenance contractors. Data analysis for the qualitative approach was conducted using content analysis, with Microsoft Word software utilized for data processing. For the first objective, the findings revealed that for the first objective is the challenges faced in using the “mill and pave” method include “ensuring quality in stabilizing the road base” and “maintaining road quality under varying weather conditions.” Second objective revealed that, the majority of respondents agreed on the method’s effectiveness in terms of “improving road surfaces” and “time efficiency”. Then, the third objective, strategies such as “education and training” and “effective project management” were identified as essential by respondents, as these can be implemented for future generations. In conclusion, this study enhances the understanding of the “mill and pave” method for road maintenance among contractors and road users. The findings of this study can serve as a reference for future research to broaden the scope of road maintenance methods for contractors, the community, and the government.